Meningkatkan Hasil Belajar Siswa Kelas XI IPS 1 dengan Menggunakan Model Pembelajaran Inkuiri Terbimbing Pada Mata Pelajaran Geografi Materi Keragaman Budaya Indonesia - Muhammad Idul; La Ode Amaluddin; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
One of the problems at Senior High School 9 Kendari is the low value of student learning outcomes caused by teaching methods that still apply conventional and teacher-centred methods. The objectives of this research are: 1) to describe the description of student learning activities taught using the Guided Inquiry learning model; 2) describe the description of the teacher's teaching activities using the Guided Inquiry learning model; and 3) describe the picture of improving learning outcomes for class XI IPS 1 students at SMAN 9 Kendari who were taught using the Guided Inquiry learning model on Indonesian Cultural Diversity material. This type of research is Classroom Action Research which is carried out in 2 cycles. Based on the data analysis, it can be concluded that: 1) the learning activity of students in cycle I was 2.52 and increased in cycle II to 3.07; 2) teacher teaching activity in cycle I was 2.97 increasing to 3.27 in cycle II; and 3) student learning outcomes in cycle I was 79% increased to 85% or as many as 28 students out of 34 students had completed.